Investigating Factors Influencing Green Purchase Intention: The Moderating Role of Green Brand Knowledge - Bernadette Carla Gita Apriani; Vonezyo Yupanzara Dharomesz (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines key determinants influencing consumers' green purchase intention, focusing on the moderating effect of green brand knowledge; specifically examines the effects of green brand positioning, green brand attitude, and environmental concern in shaping environmentally friendly product purchasing decisions towards environmentally friendly skincare brand. The data were collected with an online questionnaire distributed through purposive sampling and received 213 completed valid responses. Data analysis adopted Structural Equation Modelling (SEM) using SmartPLS version 4.0. The findings reveal that neither attitudes towards green brands nor brand positioning have a statistically significant influence over green purchase intention. Conversely, environmental concern positively and significantly predicts consumers' green purchase intention. Green brand knowledge was tested as a moderator but did not exhibit a significant moderating effect on the intercorrelations between green brand positioning, attitude toward green brands, environmental concern, and green purchase intention. These results suggest that consumers' green awareness will have a greater impact on green purchase behaviors than either brand positioning beliefs or attitudes towards green brands. The study puts forward the imperative of creating green environmental concern to facilitate green purchasing behavior and the limitations of effective green brand strategies if consumer consciousness or brand knowledge of sustainable practices is low.